ANALISIS KEPUASAN USER TERHADAP WEBSITE ADI UNGGUL BHIRAWA SURAKARTA - Yusuf Sutanto; Wing Wahyu Winarno; Andi Sunyoto (INFORMATIKA, 2014)
This study entitled Analysis is The User Satisfaction on Website Adi Unggul Bhirawa Surakarta. Case Study at STIE Adi Unggul Bhirawa Surakarta. The purpose of this research is to know how much value of hope than reality obtained (satisfaction) of students as a user facility of STIE Adi Unggul Bhirawa website for D3 Program at Information Management. Expectations of the results of this analysis will be used as a guide in the study program to evaluate and improve the accreditation process which is still accredited "C" by SK. BAN PT No: 024/BAN-PT/Ak-XI/Dpl-III/XI/2011 dated 25 November 2011. In this study, the research instruments that will be used is the End User Computing Satisfaction (EUCS). In the analysis of satisfaction with EUCS approach, divided into 5 dimensions or variables that will be investigated (unobserved), namely: Content, Format, Accuracy, Ease Of Use, Timeliness, test instruments used in research is the method of SEM, and analysis of data used by the SEM method. While the variables which will be analyzed is the D3-Information Management Students who are still active or about to graduate college.The result is students on D3 Program at Information Management were satisfaction about website www.online-aub.com. Keyword: adi unggul bhirawa, online-aub, d3 manajemen informatika